Analysis the Effect of Person-Organization Fit on Nurses' Performance at Tahlia Irham Hospital, Gowa District - Husnul Khatimah; Hasbi Ibrahim; Dwi Santy Damayati; Titi Haerana (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
Nurse performance is an important factor in supporting the quality of health services in hospitals. One of the aspects that can affect nurse performance is the compatibility between individuals and organizations or Person-Organization Fit. This study aims to analyze the influence of Person-Organization Fit on the performance of nurses at Thalia Irham Hospital, Gowa Regency. This type of research is quantitative with an ex-post facto approach. The population in this study is all nurses working at Thalia Irham Hospital, with a sample of 68 people determined through total sampling techniques. Data collection was carried out using questionnaires that have been tested for validity and reliability. The variables studied included Person-Organization Fit as an independent variable and nurse performance as a dependent variable. The data analysis technique uses a simple linear regression test to determine the influence between the two variables. The results of the analysis showed that Person-Organization Fit had a positive and significant effect on nurse performance. This is proven by a calculated t value of 4.243 which is greater than the t of the table of 1.668 and a significant value of 0.000 which is smaller than 0.05. Thus, it can be concluded that the higher the level of compatibility between individuals and organizations (Person-Organization Fit), the better the performance of nurses at Thalia Irham Hospital, Gowa Regency. ABSTRAK Kinerja perawat merupakan faktor penting dalam menunjang mutu pelayanan kesehatan di rumah sakit. Salah satu aspek yang dapat mempengaruhi kinerja perawat adalah kesesuaian antara individu dengan organisasi atau Person-Organization Fit. Penelitian ini bertujuan untuk menganalisis pengaruh Person-Organization Fit terhadap kinerja perawat di RS Thalia Irham Kabupaten Gowa. Jenis penelitian ini adalah kuantitatif dengan pendekatan ex-post facto. Populasi dalam penelitian ini adalah seluruh perawat yang bekerja di RS Thalia Irham, dengan sampel sebanyak 68 orang yang ditentukan melalui teknik total sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner yang telah diuji validitas dan reliabilitasnya. Variabel yang diteliti meliputi Person-Organization Fit sebagai variabel bebas dan kinerja perawat sebagai variabel terikat. Teknik analisis data menggunakan uji regresi linier sederhana untuk mengetahui pengaruh antara kedua variabel. Hasil analisis menunjukkan bahwa Person-Organization Fit berpengaruh positif dan signifikan terhadap kinerja perawat. Hal ini dibuktikan dengan nilai t hitung sebesar 4,243 yang lebih besar daripada nilai t tabel sebesar 1,668 dan nilai signifikansi sebesar 0,000 yang lebih kecil dari 0,05. Dengan demikian, dapat disimpulkan bahwa semakin tinggi tingkat kesesuaian antara individu dan organisasi (Person-Organization Fit), semakin baik kinerja perawat di Rumah Sakit Thalia Irham, Kabupaten Gowa.